A new portable monitor for measuring odorous compounds in oral, exhaled and nasal air - Ekuni Daisuke; Toshikawa Takara; Honda Shun-Ichi; Esaki Mitsue; Kasuyama Kenta; Tamaki Naofumi; Tomofuji Takaaki; Morita Manabu (BMC, 2011)
Abstract Background The B/B Checker®, a new portable device for detecting odorous compounds in oral, exhaled, and nasal air, is now available. As a single unit, this device is capable of detecting several kinds of gases mixed with volatile sulfur compounds (VSC) in addition to other odorous gasses. The purpose of the present study was to evaluate the effectiveness of the B/B Checker® for detecting the malodor level of oral, exhaled, and nasal air. Methods A total of 30 healthy, non-smoking volunteers (16 males and 14 females) participated in this study. The malodor levels in oral, exhaled, and nasal air were measured using the B/B Checker® and by organoleptic test (OT) scores. The VSCs in each air were also measured by gas chromatography (GC). Associations among B/B Checker® measurements, OT scores and VSC levels were analyzed using Spearman correlation coefficients. In order to determine the appropriate B/B Checker® level for screening subjects with malodor, sensitivity and specificity were calculated using OT scores as an identifier for diagnosing oral malodor. Results In oral and nasal air, the total VSC levels measured by GC significantly correlated to that measured by the B/B Checker®. Significant correlation was observed between the results of OT scores and the B/B Checker® measurements in oral (r = 0.892, p < 0.001), exhaled (r = 0.748, p < 0.001) and nasal air (r = 0.534, p < 0.001). The correlation between the OT scores and VSC levels was significant only for oral air (r = 0.790, p < 0.001) and nasal air (r = 0.431, p = 0.002); not for exhaled air (r = 0.310, p = 0.096). When the screening level of the B/B Checker® was set to 50.0 for oral air, the sensitivity and specificity were 1.00 and 0.90, respectively. On the other hand, the screening level of the B/B Checker® was set to 60.0 for exhaled air, the sensitivity and specificity were 0.82 and 1.00, respectively. Conclusion The B/B Checker® is useful for objective evaluation of malodor in oral, exhaled and nasal air and for screening subjects with halitosis. Trial registration ClinicalTrials.gov: NCT01139073